2023
DOI: 10.1109/trpms.2022.3231702
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Training, Transfer Learning and Pretext Learning for a Convolutional Neural Network Applied to Automated Assessment of Clinical PET Image Quality

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To address the issue of limited patient data, this study used transfer learning with a pre‐trained model on the ImageNet dataset. This approach allowed the model to effectively handle small datasets and still produce accurate results 24,25 . The deep U‐Net structure with a ResNet34 encoder was implemented to perform automated segmentation of CT images, which provided a useful starting point for the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the issue of limited patient data, this study used transfer learning with a pre‐trained model on the ImageNet dataset. This approach allowed the model to effectively handle small datasets and still produce accurate results 24,25 . The deep U‐Net structure with a ResNet34 encoder was implemented to perform automated segmentation of CT images, which provided a useful starting point for the study.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed the model to effectively handle small datasets and still produce accurate results. 24 , 25 The deep U‐Net structure with a ResNet34 encoder was implemented to perform automated segmentation of CT images, which provided a useful starting point for the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, transfer learning allows these large models to apply the generalized features acquired during pre-training to specific datasets under scrutiny [32]. Notably, Hopson et al [33] delved into the utilization of pre-trained CNN models for assessment of the quality of clinical PET images using transfer learning techniques. Hopson et al [33] demonstrated that pre-training significantly enhances the performance of CNN models in the task of assessing the quality of clinical images, particularly in automating the prediction of PET images.…”
Section: Pre-training and Transfer Learningmentioning
confidence: 99%